2018
DOI: 10.1117/1.jbo.23.10.107002
|View full text |Cite
|
Sign up to set email alerts
|

Spectral model for diagnosis of acute leukemias in whole blood and plasma through Raman spectroscopy

Abstract: Acute leukemias are oncohematological diseases that compromise the bone marrow and have a complex diagnostic definition, leading to a high mortality when diagnosed late. This study proposed to determine the spectral differences between whole blood and plasma samples of healthy and leukemic subjects based on Raman spectroscopy (RS), correlating these differences with their resulting biochemical alterations and performing discriminant analysis of the samples (n ¼ 38 whole blood and n ¼ 40 plasma samples). Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…The DA model was also implemented via partial least squares (PLS) regression using the whole spectral information instead of the selected PCs [32]. Multivariate models such as PCA and PLS have been used for classification of Raman spectra of sera in normal and anemia [33] and for quantification of blood analytes in human serum for diagnosis [22,23].…”
Section: Principal Component Analysis and Classificationmentioning
confidence: 99%
“…The DA model was also implemented via partial least squares (PLS) regression using the whole spectral information instead of the selected PCs [32]. Multivariate models such as PCA and PLS have been used for classification of Raman spectra of sera in normal and anemia [33] and for quantification of blood analytes in human serum for diagnosis [22,23].…”
Section: Principal Component Analysis and Classificationmentioning
confidence: 99%
“…Raman spectroscopy is based on the inelastic scattering of incident laser light by the molecules, and studies demonstrated the possibilities of the technique to determine the biochemical composition of biological tissues and fluids for qualitative (differentiation in the biochemical composition) and quantitative (differences in the concentration of selected biochemicals) analyses [ 10 , 11 , 17 , 19 , 20 ]. It can be used for cancer diagnosis [ 17 , 19 , 21 – 25 ] and cancer prognosis [ 13 , 26 , 27 ], being considered promising for showing the differences and using them to discriminate between benign and malignant tissues in different pathologies, including prostate [ 21 , 22 ], stomach [ 23 , 24 ], breast cancer [ 25 ], and skin [ 14 , 19 , 26 ], among others [ 11 , 13 , 17 , 20 , 27 ] in both in vivo and ex vivo. Raman technique does not require complicated sample preparation; it is non-invasive and non-destructive and provides information on the vibrational energy modes of molecules in real-time, allowing in situ analysis of biological tissues with high precision [ 18 , 20 , 21 ] without tissue removal [ 11 , 12 , 17 , 19 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study with blood serum samples, González-Solís et al [ 20 ] used Raman and principal component analysis (PCA) to differentiate serum from normal and leukemic patients and identify the different types of leukemia based on the biochemical composition of the serum. Silva et al [ 27 ] used whole blood and plasma samples from healthy and leukemic subjects based on Raman and PCA to differentiate leukemic and non-leukemic patients according to biochemical changes. González-Solís et al [ 20 ] and Silva et al [ 27 ] showed an increase in the concentration of plasma carotenoids in the normal group and associated this compound with a protective role against neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…The 957 cm –1 peak represents both lipid and β-carotenoids. We speculate that the antioxidant level in patients with AML and MDS is low, which is not conducive to free radical scavenging, while the high carotenoid level in healthy individuals inhibits tumors, such as AML and MDS. In the remission phase of leukemia, the plasma carotenoid level increases, which may also act as a self-protection mechanism …”
Section: Discussionmentioning
confidence: 99%